Lossy/Lossless Grounded Inductance Simulators Using Current Feedback Operational Amplifier (CFOA) - Basak, Muhammed Emin; Kacar, Firat (ISTANBUL UNIV, FAC ENGINEERING, 2018)
Active elements are critical in implementing active filters, oscillators, rectifiers, and signal processing circuits. We observe that several active circuits have been proposed in the literature. In this study, we have proposed four inductance simulators that employ only one active circuit current feedback operational amplifier and three or four passive components. The first and fourth topologies are designed for series lossy inductance, whereas the second and third topologies are designed for lossless negative inductance simulators. A passive RLC filter is used to demonstrate the effectiveness of the proposed inductance simulators.The simulations performed with the LTSpice program and the results agree with the theoretical analysis.
Keywords: CFOA; filter; CMOS; PARALLEL R-L; SINGLE; REALIZATION; SERIES; Engineering